Compañeros Dirección Editorial. - Universidad Estatal a Distancia (San José, Costa Rica : UNED, 2025)
Vitalina Hernández Ortega, Sandra Guzmán Vindas, Andrea Salazar Mesén y otros
Colección Fototeca UNED
Keywords: Hernández Ortega, Vitalina; Guzmán Vindas, Sandra; Salazar Mesén, Andrea; UNIVERSIDAD ESTATAL A DISTANCIA -- COSTA RICA; FOTOTECA